Herbal medicine use in the districts of Nakapiripirit, Pallisa, Kanungu, and Mukono in Uganda - Tabuti, John R. S.; Kukunda, Collins B.; Kaweesi, Daniel; Kasilo, Ossy M. J. (Journal of ethnobiology and ethnomedicine, 2012)
Traditional medicine (TM) occupies a special place in the management of diseases in Uganda. Not with standing the many people relying on TM, indigenous knowledge (IK) related to TM is getting steadily eroded. To slow down this loss it is necessary to document and conserve as much of the knowledge as possible. This study was conducted to document the IK relevant to traditional medicine in the districts of Mukono, Nakapiripirit, Kanungu and Pallisa, in Uganda. Methods: An ethnobotanical survey was conducted between October 2008 and February 2009 using techniques of key informant interviews and household interviews. Results: The common diseases and conditions in the four districts include malaria, cough, headache, diarrhea, abdominal pain, flu, backache and eye diseases. Respondents stated that when they fall sick they self medicate using plant medicines or consult western-trained medicine practitioners. Self medication using herbal medicines was reported mostly by respondents of Nakapiripirit and Mukono. Respondents have knowledge to treat 78 ailments using herbal medicines. 44 species, mentioned by three or more respondents have been prioritized. The most frequently used part in herbal medicines is the leaf, followed by the stem and root. People sometime use animal parts, soil, salt and water from a grass roof, in traditional medicines. Herbal medicines are stored for short periods of time in bottles. The knowledge to treat ailments is acquired from parents and grandparents. Respondents’ age and tribe appears to have a significant influence on knowledge of herbal medicine, while gender does not. Conclusion: This survey has indicated that IK associated with TM stills exists and that TM is still important in Uganda because many people use it as a first line of health care when they fall sick. Age and tribe influence the level of IK associated with herbal medicine, but gender does not.
Keywords: Ethnomedicine; Traditional medicine; Health seeking behaviour